Acupuncture in Modern Medicine - Chen, Lucy L.; Cheng, Tsung O. (IntechOpen, 2013)
This book contains four integrated sections: 1) Acupuncture Research; 2) New Developments in Acupuncture; 3) Acupuncture Therapy for Clinical Conditions and 4) Assessment and Accessibility in Acupuncture Therapy. Section 1 provides updates on acupuncture research. From acupuncture effects in modulation of immune system to the role of nitric oxide in acupuncture mechanisms, chapters in this section offer readers the newest trends in acupuncture research. Section 2 summarizes new developments in acupuncture. The included chapters discuss new tools and methods in acupuncture such as laser acupuncture, sham needles, and new technologies. Section 3 discusses acupuncture therapy for clinical conditions. The chapters in this section provide comprehensive and critical views of acupuncture therapy and its application in common clinical practice. Section 4 takes a new look at the issues related to assessment and accessibility in acupuncture therapy. These issues are central to developing new standards for outcome assessment and policies that will increase the accessibility to acupuncture therapy.